Kemampuan Tumbuhan Lakum Air (Ludwigia octovalvis) sebagai Biofiltrator Kandungan Organik di Wilayah Perairan - Rony Irawanto; Nadila Wulan Cahyani; Aunurohim; Tutik Nurhidayati; Edwin Setiawan (Berkala Ilmiah Biologi, 2023)
Indonesian waters are often faced with pollution problems caused by excess of organic content such as nitrate (NO3-) and phosphate (PO₄³⁻). For this reason, in managing these pollutants biofiltration can be applied. Biofiltration is a method for treating waste biologically and plants can be applied in reducing the content of pollutants Biofiltration can be done using. Therefore, we introduced “Lakum Air” plant (Ludwigia octovalvis) as biofiltrator for reducing organic content of nitrate (NO3-) and phosphate (PO₄³⁻). L. octovalvis were cultivated in media with addition of NO3- and PO₄³⁻ 10 mg/L respectively. The results displayed L. octovalvis in NO3- possessed an average reduction ith efficiency of 0% for 2 weeks contact time and 0.5% for 4 weeks. At the same time in PO₄³⁻, L. octovalvis possessed an average reduction with efficiency of 35% for 2 weeks contact time and 58% with 4 weeks. Moreover, L. octovalvis can absorb NO3- with an average of 2.99 mg/L in 2 weeks contact time and 5.92 mg/L in 4 weeks. Likewise, L. octovalvis absorb PO₄³⁻ with an average of 4.72 mg/L for 2 weeks contact time and 6.66 mg/L for 4 weeks.